2019
DOI: 10.3390/w11122614
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vegetation Successional Status on Slope Runoff Erosion in the Loess Plateau of China

Abstract: Slope vegetation restoration is known to influence erosion in the Loess Plateau region in China. The ability of vegetation to mitigate soil erosion under extreme runoff, however, has not been studied in great detail in this region. Here, we examine five typical vegetation communities in the Loess Plateau region that originated from restoration efforts enacted at different times (1, 11, 15, 25, and 40 years). Water scouring experiments were carried out to monitor vegetation community succession and its effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In the past few decades, many scholars have made many efforts to study the process and mechanism of soil erosion, establish many soil erosion prediction models and try to control soil erosion [4][5][6][7]. At present, a set of soil erosion control measures system integrating engineering measures, agricultural measures, and biological measures has been formed [8][9][10], especially vegetation measures play an extremely important role in soil erosion control [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, many scholars have made many efforts to study the process and mechanism of soil erosion, establish many soil erosion prediction models and try to control soil erosion [4][5][6][7]. At present, a set of soil erosion control measures system integrating engineering measures, agricultural measures, and biological measures has been formed [8][9][10], especially vegetation measures play an extremely important role in soil erosion control [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The speciesrich and diverse vegetation community have a larger root morphology so that it can control erosion (Ford et al 2016). The results of the study by Chang et al (2019) also showed that the development of vegetation roots could significantly reduce the total amount of runoff.…”
Section: Vegetation Diversitymentioning
confidence: 98%
“…Soil erosion occurred in areas where intense interactions among strata at the surface of land and environmental factors interact including water, wind, freeze-thaw, gravity, etc. [5][6][7]. Freeze-thaw erosion was the result of frequent changes in temperature, resulting in changes to soil and rock physico-chemical properties and occurs to a greater extent at high altitudes and latitudes in cold regions [8,9].…”
Section: Introductionmentioning
confidence: 99%